2008
DOI: 10.1107/s1600536808022897
|View full text |Cite
|
Sign up to set email alerts
|

Propane-1,3-diammonium bis[aquachlorido(4-hydroxypyridine-2,6-dicarboxylato-κ3O2,N,O6)mercurate(II)] tetrahydrate

Abstract: The reaction of mercury(II) chloride dihydrate, propane-1,3-diamine and 4-hydroxy­pyridine-2,6-dicarboxylic acid in a 1:1:1 molar ratio in aqueous solution, resulted in the formation of the title compound, (C3H12N2)[Hg(C7H3NO5)Cl(H2O)]2·4H2O or (pnH2)[Hg(hypydc)Cl(H2O)]2·4H2O (where pn is propane-1,3-diamine and hypydcH2 is 4-hydroxy­pyridine-2,6-dicarboxylic acid). The metal atom is coordinated by one chloride group, one water mol­ecule cis to the chloride ligand and one (hypydc)2− ligand. The coordinated wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…effects from the bulky ligands. The Hg-O bond lengths are in agreement with those found in related Hg(II) complexes (Guo & Dong, 2009;Aghabozorg, et al, 2008)…”
Section: X-wz Thanks Zhengzhou University Of Light Industry For Reseasupporting
confidence: 88%
See 1 more Smart Citation
“…effects from the bulky ligands. The Hg-O bond lengths are in agreement with those found in related Hg(II) complexes (Guo & Dong, 2009;Aghabozorg, et al, 2008)…”
Section: X-wz Thanks Zhengzhou University Of Light Industry For Reseasupporting
confidence: 88%
“…For the synthesis, see: Xiao et al (2004); Xie et al (2002). For bond lengths related mercury compounds, see: Guo & Dong (2009); Aghabozorg, et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…Our research group has previously reported several proton-transfer compounds using pyridine-2,6-dicarboxylic acid (pydcH 2 ), propane-1,2-diamine (p-1,2-da) and propane-1,3-diamine (p-1,3-da), including (p-1,2-daH 2 )(pydcH) 2 .2H 2 O (Aghabozorg et al, 2008d) (Aghabozorg et al, 2008a)…”
Section: S1 Commentmentioning
confidence: 99%
“…For related structures, see: Aghabozorg et al (2007Aghabozorg et al ( , 2008a; Hall et al (2000); Ramos Silva et al (2008); Soleimannejad et al (2009); Zhou et al (2003Zhou et al ( , 2007; Zou et al (2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: SMART (Bruker, 2007); cell refinement: SAINT-Plus (Bruker, 2007); data reduction: SAINT-Plus; program(s) used to solve structure: SHELXTL (Sheldrick, 2008); program(s) used to refine structure: SHELXTL; molecular graphics: SHELXTL; software used to prepare material for publication: SHELXTL. (Hall et al, 2000) and (tataH) 2 [Cu(Hchel) 2 .6H 2 O (tata = 2,4,6-triamino-1,3,5-triazine) (Ramos Silva et al, 2008) (Zhou et al, 2003), [Zn 3 (chel) 2 .8H 2 O] n (Zou et al, 2009) (Aghabozorg et al, 2007), and the most similar to the title compound, (pnH 2 )[Hg(Hchel)Cl(H 2 O)] 2 .4H 2 O (pn = propane-1,3-diamine) (Aghabozorg et al, 2008a).…”
Section: Tablementioning
confidence: 99%